Low emission development strategies for agriculture and other land uses: The case of Colombia - De Pinto, Alessandro; Haruna, Akiko; Creamer, Bernardo; Hyman, Glenn; Li, Man; Kwon, Ho Young; Garcia, Jhon Brayan Valencia; Coca, Alejandro Castro; Tapasco, Jeimar; Martinez, Jesus David; Hoyos, Jesus David (International Food Policy Research Institute, 2014)
The purpose of the work presented in this report is to demonstrate that policymakers have tools at their disposal that provide significant help in the evaluation of trade-offs, opportunities, and repercussions of the policies under consideration. This report focuses on Colombia, however the analytical framework can be applied to any country interested in exploring country-wide effects and economic viability of policies that aim to reduce GHG emissions from agriculture. Results provided in this study should be seen as an example of the potential applications of the framework developed. We were able to identify policies covering the entire spectrum of potential outcomes: win-win policies (reduce land allocated to pasture), policies with tradeoffs (reduce deforestation in the Amazon) and policies that seem to generate clearly inferior results (increase the area allocate to palm cultivation).